Soluble guanylate cyclase is activated differently by excess NO and by YC-1: Resonance Raman spectroscopic evidence - Ibrahim, Mohammed (2010)
Modulation of soluble guanylate cyclase (sGC) activity by nitric oxide (NO) involves two distinct steps. Low level activation of sGC is achieved by the stoichiometric binding of NO (1-NO) to the heme cofactor, while much higher activation is achieved by the binding of additional NO (xsNO) at a non-heme site. Addition of the allosteric activator YC-1 to the 1-NO form leads to activity comparable to xsNO state. In this study the mechanisms of sGC activation were investigated using electronic absorption and resonance Raman (RR) spectroscopic methods. RR spectroscopy confirmed that the 1-NO form contains 5-coordinate NO-heme and showed that the addition of NO to the 1-NO form has no significant effect on the spectrum. In contrast, addition of YC-1 to either the 1-NO or xsNO forms alters the RR spectrum significantly, indicating a protein-induced change in the heme geometry. This change in the heme geometry was also observed when BAY 41-2272 was added to the xsNO form. Bands assigned to bending and stretching motions of the vinyl and propionate substituents change intensity in a pattern suggesting altered tilting of the pyrrole rings to which they are attached. In addition, the N-O stretching frequency increases, with no change in the Fe-NO frequency, an effect modeled via DFT calculations as resulting from a small opening of the Fe-N-O angle. These spectral differences demonstrate different mechanisms of activation by synthetic activators, such as YC-1 and BAY 41-2272, and excess NO.